Studi Kasus Penerapan Inhalasi Diffuser dengan Aromaterapi Peppermint dalam Peningkatan Bersihan Jalan Napas pada Anak dengan Bronkop Neumonia di Paviliun Ade Irma Suryani Lantai II - Sofwan Sofwan (Pusat Riset dan Inovasi Nasional, 2024)
Bronchopneumonia is an infectious disease of the lower airway that occurs in the bronchi and alveolus. Bronchopneumonia is a serious problem in children, with 278,260 children under five years old affected by bronchopneumonia in 2021. The priority problem that arises in bronchopneumonia is ineffective airway clearance. One of the efforts made to overcome ineffective airway clearance is through non-pharmacological therapy. Non-pharmacological therapy that can be used is the application of peppermint aromatherapy diffuser inhalation to overcome airway clearance. This case study design aims to determine the results of the application of peppermint aromatherapy diffuser inhalation in overcoming ineffective airway clearance. The method of data collection techniques in this paper uses interview techniques, documentation, observation and physical examination. The results of this case study were obtained, namely in An.S before being given the peppermint aromatherapy diffuser inhalation action on day 1 to day 5, the average respiratory frequency was 49.6x/minute, the sound of ronchi was present on days 1 to 3, unable to remove sputum after being given peppermint aromatherapy diffuser inhalation, the average respiratory frequency was 44x/minute. The ronchi sound was not heard on days 4 and 5, and the child easily expelled sputum. The case study conclusion of the application of peppermint aromatherapy diffuser inhalation proved effective in overcoming ineffective airway clearance.